Hemp seed oil: Minor components and oil quality. Issue 10 (29th September 2015) - Liang, Jingbang; Appukuttan Aachary, Ayyappan; Hollader, Usha‐Thiyam
<x xml:space="preserve">Abstract</x> Owing to its high content of omega‐6/omega‐3 fatty acids and bioactive minor components with antioxidant activities, hemp seed oil is now recognized for its health benefits by a large number of consumers. This paper primarily discusses the profile of minor components in hemp seed oil and their beneficial and adverse effects on oil quality. While tocopherols, polyphenols and phytosterols prevent oxidative deterioration of hemp seed oil, the high amount of chlorophyll can be detrimental to oil quality.